ҚОРАҚАЛПОҒИСТОН ШОРОИТИДА ЭЧКИЛАР (CAPRA HIRCUS L.) ГЕЛЬМИНТЛАРИ ТУР ТАРКИБИ ВА УЛАРНИНГ ОРГАНИЗМДА ТАҚСИМЛАНИШИ - Палўаниязова, Д.А.; Дадаев, С.; Қаниязов, А.Ж. (SCIENCE and SOCIETY, 2023)
It was revealed that 29 species of helminths belonging to 21 genera, 14 families, 9 families, 3 classes and 2 species parasitize goats in the conditions of Karakalpakstan. The largest number of identified helminths, i.e. 19 species belong to the class of nematodes (66%), 7 species to the class of cestodes (24%) and 3 species to the class of trematodes (10%).